The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/978-3-642-38919-1_4
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Function of Respiratory Syncytial Virus Surface Glycoproteins

Abstract: The two major glycoproteins on the surface of the RSV virion, the attachment glycoprotein (G) and the fusion (F) glycoprotein, control the initial phases of infection. G targets the ciliated cells of the airways, and F causes the virion membrane to fuse with a target cell membrane. The F protein is the major target for antiviral drug development, and both G and F glycoproteins are the antigens targeted by neutralizing antibodies induced by infection. In this chapter we review the structure and function of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
293
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(301 citation statements)
references
References 102 publications
3
293
0
5
Order By: Relevance
“…HRSV Glycoprotein protein (G): this protein is involved in virus attachment 114 and it also exists as a secreted form, which prevents opsonization and neutralization of hRSV by anti-G specific antibodies. Moreover, the secreted form of the G protein has a chemokine-like motif (CX3C) that competes with fractalkine (CX3CL1) in binding to its receptor CX3CR1, thus reducing the CX3CR1 C T cells response.…”
Section: Role Of Hrsv Proteins In Immunomodulationmentioning
confidence: 99%
“…HRSV Glycoprotein protein (G): this protein is involved in virus attachment 114 and it also exists as a secreted form, which prevents opsonization and neutralization of hRSV by anti-G specific antibodies. Moreover, the secreted form of the G protein has a chemokine-like motif (CX3C) that competes with fractalkine (CX3CL1) in binding to its receptor CX3CR1, thus reducing the CX3CR1 C T cells response.…”
Section: Role Of Hrsv Proteins In Immunomodulationmentioning
confidence: 99%
“…The F protein of RSV is a 574 amino acids class I fusion glycoprotein similar to influenza virus hemagglutinin and HIV -1 envelope glycoprotein 11,12) . It is synthesized as a precursor F 0 and cleaved by the furin -like host protease to produce F 1 and F 2 subunits 13,14) .…”
Section: F Proteinmentioning
confidence: 99%
“…The mature protein contains three copies of two polypeptides (F 1 and F 2 ). After initially folding into a metastable prefusion conformation (pre -F), RSV F undergoes a structural change naturally or in the process of infection, and eventually acquires a stable postfusion conformation (post -F) 12) . Recently, cryoelectron tomography of cell culturegrown RSV has revealed that pre -F and post -F are present on the virion surface.…”
Section: F Proteinmentioning
confidence: 99%
“…Anchored by a hydrophobic transmembrane domain at its C terminus, F 1 comprises the hallmark features of a type 1 fusion protein, having a hydrophobic fusion peptide (FP) at the N terminus and two major heptad repeats, A and B (HRA and HRB, respectively), that ultimately refold to form the hyperstable six-helix bundle (6HB) that constitutes the fusion core of the postfusion structure. Triggering of the protein is thought to be provoked by receptor engagement, which prompts the release of the hydrophobic FP into the target membrane and the accompanied elongation of the HRA helices beyond the head of the protein (10,11). Refolding of HRA and HRB brings the viral and host membranes into close proximity, resulting in membrane fusion driven by the energy difference between the pre-and postfusion conformations of the protein (10,11).…”
mentioning
confidence: 99%
“…Triggering of the protein is thought to be provoked by receptor engagement, which prompts the release of the hydrophobic FP into the target membrane and the accompanied elongation of the HRA helices beyond the head of the protein (10,11). Refolding of HRA and HRB brings the viral and host membranes into close proximity, resulting in membrane fusion driven by the energy difference between the pre-and postfusion conformations of the protein (10,11). In addition to facilitating the fusion of viral and cellular membranes, cell surface F protein also drives fusion between infected and neighboring cells, resulting in the formation of large multinucleated cells, or syncytia (12,13).…”
mentioning
confidence: 99%